2021
DOI: 10.2147/jaa.s318017
|View full text |Cite
|
Sign up to set email alerts
|

Imbalanced Coagulation in the Airway of Type-2 High Asthma with Comorbid Obesity

Abstract: Asthma is a common, chronic airway inflammatory disease marked by airway hyperresponsiveness, inflammation, and remodeling. Asthma incidence has increased rapidly in the past few decades and recent multicenter analyses have revealed several unique asthma endotypes. Of these, type-2 high asthma with comorbid obesity presents a unique clinical challenge marked by increased resistance to standard therapies and exacerbated disease development. The extrinsic coagulation pathway plays a significant role in both type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 118 publications
(204 reference statements)
0
2
0
Order By: Relevance
“…In addition, studies have shown the upregulation of tissue factor by IL-13 in Th2-type asthma [ 36 ] and enhanced thrombin formation [ 37 ], contributing to a pro-coagulant environment. Several human studies have reported presence of an excessive pro-coagulation activity in the airways with plasma exudation as a potential source of the pro-coagulation proteins, particularly in severe asthma [ 36 , 38 40 ]. Also, complementary studies in small animal models indicate vascular leak in inflammation is produced by cell state changes of capillary pericytes [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have shown the upregulation of tissue factor by IL-13 in Th2-type asthma [ 36 ] and enhanced thrombin formation [ 37 ], contributing to a pro-coagulant environment. Several human studies have reported presence of an excessive pro-coagulation activity in the airways with plasma exudation as a potential source of the pro-coagulation proteins, particularly in severe asthma [ 36 , 38 40 ]. Also, complementary studies in small animal models indicate vascular leak in inflammation is produced by cell state changes of capillary pericytes [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients may also show food residues in the oral cavity [ 70 ], a large food bolus construct [ 27 , 31 ], gastroesophageal reflux disease [ 32 , 44 , 83 ], and oropharyngeal dysphagia (OFD) [ 55 ], a symptom that refers to the difficulty in forming or moving the food bolus toward the pharyngeal wall or toward the esophagus and which is concurrently related to difficulty in oral propulsion. OFD causes alterations in safety (possible aspiration pneumonia) and efficacy (dehydration and malnutrition), thereby increasing the morbidity and mortality of individuals experiencing this condition and, consequently, deteriorating their quality of life [ 46 , 73 ]. Other features of the swallowing function in obese patients include esophagitis or inflammation, which damages the duct that extends from the throat to the stomach [ 83 ], and binge eating disorder or compulsive behavior through binge eating, where the main characteristic is loss of control over what is eaten [ 43 , 71 ].…”
Section: Discussionmentioning
confidence: 99%